Skazani na karę śmierci przez Specjalny Sąd Karny w Katowicach w latach 1945–1946 - Dziurok, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The purpose of this article is to present issues related to capital punishment in the jurisprudence of the Special Criminal Court in Katowice — one of nine special courts established to try “fascist and Nazi criminals” and traitors to the Polish nation. Records of death penalty trials, prisoners’ files from penal institutions, convict records, and articles in regional press were subject to scrutiny, which enabled establishing the names of 57 (or 58) people sentenced to death by the Special Criminal Court in Katowice between March 1945 and November 1946. The majority of the convicts were accused of denunciation to the German authorities, participation in arrests, and, in just three cases, murder. The Katowice Court was one of the special courts with the fewest instances of capital punishment. Thirty-two death sentences were carried out, and the remaining convicts (who constituted 40% of the total) were pardoned by the decision of the President of the National Council and left prison no later than in 1956.
Keywords: Specjalny Sąd Karny w Katowicach; zbrodniarze faszystowsko-hitlerowscy; zbrodnie niemieckie; kara śmierci; dekret sierpniowy